Microstructural, mechanical and corrosion behavior of UNS S31803/ Hastelloy C-276 dissimilar metal welds - Atapek, S. Hakan; Tumer, Mustafa; Clikkol, Emrullah; Kisasoz, Alptekin; Kerimak, M. Zaim (ELSEVIER, 2023)
In this study, UNS S31803 duplex stainless steel and Hastelloy C-276 nickel-based superalloy were joined by gas tungsten arc welding (GTAW) process. Nickel based ERNiCr-3 and ERNiCrMo-3 filler metals with dif-ferent chemical compositions were used for joining the dissimilar metals. Metallurgical structures of the joint parts were determined by microstructural characterization studies. In mechanical characterization, both hardness and impact toughness were measured. Corrosion behavior of the welds were investigated by potentiodynamic polarization tests in 3.5% NaCl solution. Characterization studies showed that (i) weld metals had a dendritic/cellular solidification structure which changed due to thermal effects in all passes from the surface to the root, (ii) depending on the chemical composition of the filler metal, Nb-rich carbides and Laves phase were formed in the weld metal, (iii) the amount of Mo affected toughness, hardness, and corrosion resistance.(c) 2022 CIRP.
Keywords: Dissimilar weld; UNS S31803; Hastelloy C-276; GTAW; Characterization; Hastelloy; STAINLESS-STEEL; INCONEL 625; NICKEL-ALLOY; SAF 2507; WELDMENTS; RESISTANCE; JOINTS; TEMPERATURE; EVOLUTION; STRENGTH; Engineering